PENGEMBANGAN INSTRUMEN EVALUASI KEMAMPUAN BERPIKIR KRITIS PADA MATERI PERBANDINGAN - Iis Istiqomah; Nurjanah Nurjanah (Universitas Islam Nusantara, 2022)
This research is an alternative to overcome the low critical thinking skills, namely the development of evaluation tools to measure student’s critical thinking skills. This research and development begins with determining the research objectives, namely developing a critical thinking ability test and knowing the validity, reliability, discriminating power, and level of difficulty of the test. Critical thinking ability evaluation instrument on comparative material for class VII Junior High School include in Research and Development (RD). The RD model used is the Thiagarajan 3D model, which includes 3 stages namely: define, design, and develop. The instrument in this study were critical thinking skills test and validation sheets. The subject of this research is class VII 31 Junior High School Bandung, totaling 15 people. The assesment instrument developed is in the form of descriptive questions. The data from the validation of the instrument’s feasibility by the expert is declared valid. The results of the analysis of the validity of the items based on the results of the analysis of the validity of items using the Product Moment correlation technique can be seen that the level of validity of the evaluation instrumen is declared high, while the reability value of 0,72 with a high interpretation. Analysis of the difficulty level of the instrumen obtained an average scor of 0,22-0,54 in medium-difficult category. The discriminatory power of the instrumen shows a sufficient category with an average value of 0,31-0,78.